Автоматизація технологічного процесу обробки інформації в сучасних умовах - Батюк, А. Є.; Кравчук, Г. Т. (Видавництво Державного університету "Львівська політехніка", 2000)
In article the modern means of automation of technological processes of the tax, transfer, preservation and processing of the information are described, the technique of account of parameters of an estimation of efficiency of introduction of the automated technology of processing of the information is offered.